Precipitation-derived effects on the characteristics of proteinaceous soil organic matter across the continental United States - Hong, Hualong; Ma, Li; Smith, David B.; Lu, Haoliang; Yan, Chongling; Xia, Kang; Williams, Mark A. (Frontiers in Soil Science, 2022)
Proteinaceous amino acids composed up to 50% of microbial biomass, are a primary building block of soil organic nitrogen, and play a key role in soil organic N-C cycling and accrual. However, the large-scale drivers on these organic nitrogen pools is less explored. We hypothesized that the trends related to vegetation, soil mineralogy and climate will change the composition of hydrolyzable amino acids (HAAs), both within and between each horizon. Herein we report on the patterns of HAAs, and their dependence on soil (e.g., Al, Fe, pH) and climate (e.g., precipitation) factors between soil horizons across the continental U.S. It was found that the effect of vegetation type on HAAs was greater in the A horizon than in the C horizon, which was related to the different stages of the vegetation-associated decomposition and pedogenesis processes. A similar Leu-Phe-Ile-Gly co-occurrence structure was found in both soil horizons suggesting some similarity in processes that enrich organics in soil. Precipitation, but not temperature, showed significant associations with HAA composition. The chemical properties of the soil, including pH and mineral metals (Fe, Mn, Al, Ca), also influenced the HAAs’ characteristics. In particular, some specific HAAs (Glx, Asn, and Ala) mainly reflected the HAAs’ response to the environmental gradients in both horizons. The effect of precipitation on HAAs exhibits as a complex relationship mediated through organic matter, pH and minerals. To our knowledge, this is the first study to assess continental-wide descriptors of the largest soil organic N pool, showing that pH, Fe, Ca, precipitation and vegetation explain soil AA composition. The role played by each of these drivers in the accrual and turnover of organic matter over large regional scales deserve further scrutiny. The large surface and subsurface HAA data set from this study should help change the way micro-scale conceptual and mechanistic models describe the chemical interactions and source pools that drive soil organic nitrogen, and possibly soil organic matter composition over regional scales.